catena-Poly[[[aqua(pyrazine-2-carboxamide-κ(2) N (1),O)zinc]-μ-pyrazine-2-carboxamide-κ(3) N (1),O:N (4)] dinitrate] - Shirvan, Sadif A. (International Union of Crystallography, 2012)
In the crystal of the title compound, {[Zn(C(5)H(5)N(3)O)(2)(H(2)O)](NO(3))(2)}(n), the Zn(II) cation is N,O-chelated by two pyrazine-2-carboxamide (PCA) ligands and is further coordinated by one water molecule and by one pyrazine-N atom from an adjacent PCA ligand in a distorted ZnN(3)O(3) octahedral geometry. One of the two independent PCA ligands bridges two Zn(II) cations, forming a zigzag polymeric chain running along the c axis. In the crystal, the NO(3) (−) anions link to the chain via O—H⋯O and N—H⋯O hydrogen bonding. Weak intermolecular C—H⋯O interactions also occur.